The influence of the method of felling on the process of natural regeneration in the conditions of the wet fir forest of the Pokutsky Carpathians - Vanjurak, P. I. (Forestry Education and Science: Current Challenges and Development Prospects, 2024)
The number and species composition of the undergrowth were determined in three plots with different felling methods, as well as in the control plot. The obtained results for section No. 3, where group-selective felling was carried out, confirm the satisfactory state of natural regeneration of spruce and fir in particular, and the good state of the section as a whole. Conducting the first method of group-selective felling provided a positive result regarding the number of reliable undergrowth on the site.A good state of natural regeneration was recorded for both spruce and fir in section No. 4 (uniform and gradual felling). Fir undergrowth was recorded 2.7 times more than spruce. Beneficial undergrowth on this section is 3.3 times more than on the section with group-selective felling.A very high amount of reliable undergrowth was recorded on section #2 with narrow-cut felling. A good state of natural regeneration was recorded for both forest-forming main tree species, but with a very high advantage of spruce over fir - 8.3 times. The number of promising undergrowth here is 2.3 times greater than on the section with uniform and gradual felling.On the control plot, only the growth of white fir was assessed as insufficient, while the growth of all other tree species was classified as unsatisfactory.Based on the results of the research, it is possible to recommend a 40-50 m wide narrow larch felling as such, which provides a significant amount of reliable spruce growth on the site, without revealing a significant negative impact on the environment.